The use of creative graphic tasks is in the process of preparation of future teachers of technologies to project activity (Pedagogy of Higher and Secondary Education, 2012)
Gedzyk А. The use of creative graphic tasks is in the process of preparation of future teachers of technologies to project activity.In the article possibilities of optimization of professional preparation of future teachers of technologies are analysed to project activity by facilities of creative graphic tasks, which must be based on principles, that the conceptions of the system of activation of studies fixed in basis and which embrace the basic aspects of educational-educator process.
Keywords: professionally-graphic preparation; project activity; designer knowledge; optimization of educational process; typology of tasks